TEKNIK PENYUSUNAN LAPORAN ANALISIS MUTU PENDIDIKAN ISLAM: TEKNIK PENYUSUNAN LAPORAN ANALISIS MUTU PENDIDIKAN ISLAM - Muhammad Shaiful Bahri; M. Sobry (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine systematic and objective techniques for preparing quality analysis reports in Islamic education, aligned with established educational evaluation standards. In the effort to enhance the quality of Islamic educational institutions, a quality analysis report serves as a crucial foundation for decision-making, strategic planning, and continuous improvement. The research employs a literature review, observation of reporting practices in Islamic educational institutions, and analysis of educational quality documents. The findings indicate that preparing a quality analysis report for Islamic education requires attention to three key aspects: (1) formulation of quality indicators based on Islamic principles and national education standards; (2) valid, reliable, and measurable data collection and processing; and (3) presentation of analytical results in a communicative and actionable format. Moreover, the involvement of stakeholders—including teachers, administrators, and the community—is essential to ensure the objectivity of the report. The study concludes that implementing proper reporting techniques significantly strengthens internal quality assurance systems and enhances the accountability of Islamic educational institutions in delivering quality education services.